Optimalisasi Penguatan Kapasitas Kewirausahaan Digital Komunitas Single Mother melalui Workshop Desain Grafis berbasis Artificial Intelligence - Fatmariani Fatmariani; Azalia Mawarindani Indra; Eka Prasetya Adhy Sugara (JPM: Jurnal Pengabdian Masyarakat, 2026)
The development of digital technology requires micro-businesses to be able to utilize digital media as a means of product promotion and marketing. However, members of the Single Mother Ukhuwah Community in Palembang City still face limitations in utilizing digital technology, especially in creating attractive promotional media and using Artificial Intelligence (AI)-based applications. This condition results in suboptimal product promotion, resulting in low business competitiveness. This community service activity aims to strengthen the digital entrepreneurship capacity of community members through an AI-based graphic design workshop. The implementation method uses a participatory approach that includes identifying partner needs, delivering digital entrepreneurship materials, training in the use of AI-based graphic design applications, practicing creating digital promotional content, mentoring, and evaluation through pre-tests and post-tests. The evaluation is carried out on five indicators, namely understanding digital marketing, using AI applications, the ability to create promotional designs, utilizing social media, and confidence in using digital technology. The results of the activity showed improvements across all indicators: digital marketing understanding increased from 40% to 85%, AI application usage increased from 25% to 82%, promotional design skills increased from 30% to 88%, social media utilization increased from 45% to 90%, and technology confidence increased from 38% to 87%. Furthermore, all participants were able to produce digital promotional content tailored to their business characteristics and began utilizing social media as a more effective marketing tool. These results demonstrate that the AI-based graphic design workshop was effective in increasing the digital entrepreneurship capacity of the single mother community and supporting the development of more competitive micro-enterprises in the digital era.